PAHAM YESUS KRISTUS MENURUT ATHANASIUS DARI ALEKSANDRIA DALAM CONTRA GENTES DE INCARNATIONE - Hendri Mulyana Sendjaja (Jurnal Orientasi Baru, 2012)
In his double treatise, Contra Gentes and De Incarnatione, Athanasius proposes a Logos Christology from the soteriological perspective. According to him, Christ is the Logos of God, Fathers proper offspring, the only Fathers Begotten Son, the Unchanging Image of the Father. Christ as the Logos of God does Gods works, both Creation, Providence and Salvations works. In His Salvation work, by the works indicated through His human body, Jesus Christ, the Incarnate Logos, does the Gods works, reveals God who is good, who is the lover of humanity, to human that fall into sin. Jesus surrenders His own body as an offering and a sacrifice for the sake of salvation of all creation.